(untitled) (Trabalho & Educação, 2017)
This research analyzes the effectiveness of policies and practices of professional training of women deprived of liberty, instituted in Minas Gerais, specically in the prison units of the Metropolitan Region of Belo Horizonte. The dissertation contemplates discussions about the historical correlation between the mode of production of material life and punitive forms, public policies of work and education in the prison system, social relations of sex and the sexual division of labor, imprisonment of women, among others. These themes are approached based on the contributions of Karl Marx, theorists of marxist afliation and researchers of the line “Labor and Education”. A qualitative research was carried out, based on the documentary analysis and semi-structured interviews with 14 women deprived of freedom who... ___ Esta pesquisa analisa a efetividade das políticas e das práticas de formação prossional das mulheres privadas de liberdade, instituídas em Minas Gerais, especicamente nas unidades prisionais da Região Metropolitana de Belo Horizonte. A dissertação contempla as discussões sobre o correlacionamento histórico entre o modo de produção da vida material e as formas punitivas, as políticas públicas de trabalho e educação no sistema prisional, as relações sociais de sexo e a divisão sexual do trabalho, o encarceramento das mulheres, entre outras. As referidas temáticas são abordadas com base nas contribuições de Karl Marx, de teóricos de liação marxista e de pesquisadores da linha “Trabalho e Educação”. Realizou- se uma pesquisa de abordagem qualitativa, a partir da análise documental e da realização de entrevistas semiestruturadas com 14 mulheres privadas de liberdade que...